The Structure of Conceptual Metaphor in the Holy Qur’an: (A Cognitive Linguistic Account) - Ejlal Ishaq Yousef Alshennawi (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This research focuses on analyzing metaphors in some verses of the Holy Qur’an. It also examines how metaphors are characterized and structured with reference to Conceptual Metaphor Theory, a theoretical framework originated by George Lakoff and Mark Johnson. This analysis is based on the cognitive semantic approach towards metaphor. The study concludes that all types of conceptual metaphor, namely structural, orientational and ontological, were found in the Holy Qur’an. The results showed that the Holy Qur’an is rich in metaphors of all types, and the most frequently occurring type of conceptual metaphor is structural metaphor. The findings also reveal that conceptual metaphors in the Holy Qur’an appear across different grammatical categories, including nouns, verbs, adjectives and prepositions. The results further demonstrated that conceptual metaphors in the Holy Qur’an fulfil one of the three meta-functions of language that were proposed by Haliday (1973).